Mangrove Landscaping As An Adaptation Pattern To Reduce The Impact of Climate Change in Segara Anakan Lagoon, Cilacap Regency Indonesia (Baghdad Science Journal, 2024)
Mangrove landscaping in the Segara Anakan Lagoon (SAL) is an adaptation pattern of mangrove ecosystems to live and grow in unstable areas. This research aimed to develop a mangrove landscape to mitigate the impacts of ocean waves, currents, and inundation due to climate change. The study was conducted in SAL and Cilacap Coast (CC) using the environmental properties and climate change data. The data obtained were analyzed using mapping and trendline analyses. The results showed that mangrove landscaping in Segara Anakan had four zones with Nypa frutican, Rhizophora styllosa, Aegiceras corniculatum, Rhizophora apiculata, Avicennia marina, Sonneratia alba identified as the best adaptation of mangrove species. Climate change give a high impact on mangrove degradation (degradation 142.1 ha/year), the instability of rainfall intensity with average intensity 3552 mm/year, irregular wind direction with a speed average of 7 knots, and increasing of sea wave and sea level rise (range from 2.7 m to 3.4 m) The results conclude that the mangrove species have ability to live and grow, because the climate change does not affect mangrove growth (the correlation with rainfall intensity = -0,35, with wind speed = 0,18 and sea wave = - 0,34).